Unraveling the Underlying Interaction Mechanism Between Dabie bandavirus and Innate Immune Response - Zhou, Chuan-min; Yu, Xue-jie (Frontiers in Immunology, 2021)
The genus Bandavirus consists of seven tick-borne bunyaviruses, among which four are known to infect humans. Dabie bandavirus, severe fever with thrombocytopenia syndrome virus (SFTSV), poses serious threats to public health worldwide. SFTSV is a tick-borne virus mainly reported in China, South Korea, and Japan with a mortality rate of up to 30%. To date, most immunology-related studies focused on the antagonistic role of SFTSV non-structural protein (NSs) in sequestering RIG-I-like-receptors (RLRs)-mediated type I interferon (IFN) induction and type I IFN mediated signaling pathway. It is still elusive whether the interaction of SFTSV and other conserved innate immune responses exists. As of now, no specific vaccines or therapeutics are approved for SFTSV prevention or treatments respectively, in part due to a lack of comprehensive understanding of the molecular interactions occurring between SFTSV and hosts. Hence, it is necessary to fully understand the host-virus interactions including antiviral responses and viral evasion mechanisms. In this review, we highlight the recent progress in understanding the pathogenesis of SFTS and speculate underlying novel mechanisms in response to SFTSV infection.